RESEARCH OF CONSTRUCTIVE-TECHNOLOGICAL SOLUTIONS OF NATIONAL SHIRTS FOR DECORATION OF MODERN WOMEN'S DRESSES OF ETHNO-STYLE - ZASORNOVA, IRYNA; OCHKURENKO, VICTOR; ZASORNOV, ALEXANDER; TIELUSHKINA, OLHA; SARANA, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The research of different types of Ukrainian national women's shirts of the Boykiv region at the end of the XIX and the beginning of the XX century about constructive-technological decisions and used colours of materials is carried out in the work.The main types of cut of national shirts of Boykivshchyna have been studied: shirt with shoulder inserts, tunic-like shirt, shirt with one-piece sleeves, shirt with coquette.The authors have developed a classifier of structural elements of the Ukrainian national shirts of Boykivshchyna. Based on the developed classifier, a massive of structural elements of Ukrainian national shirts of Boykivshchyna was formed, which contains information on types of shirt cuts, their silhouettes, length of shirts, types of sleeves by shape and length, types of collars and neck shapes.The proposed massive can be expanded and supplemented, provided that further research will reveal some more structural elements of traditional shirts. Using the structural elements of the massive, it is possible to create new models of modern women's dresses, introducing them into mass production. Combining design elements, it is possible to create different versions of models of women's dresses for implementation in multimodal flows.The results of research on determining the colour scheme of materials used for the manufacture of national shirts of Boykivshchyna are presented. It was determined that the most common colours were: blue, beige, white and burgundy. Colours such as red, black, brown, blue, and green were less common.RGB-parameters of shades of colours of materials which are offered to use at designing of the modern women's dresses made in ethno-style are defined.According to the results of the research, sketches of three models of women's dresses were developed. Model A of a modern women's dress, made in ethno style, sewn in industrial conditions.
Keywords: national shirt; classifier; women's dress; embroidery; design and technological solutions; colour; frequency; RGB parameters